Electro-Optical Switching of Dual-Frequency Nematic Liquid Crystals: Regimes of Thin and Thick Cells - Olha Melnyk (Crystals, 2019)
Conventional display applications of liquid crystals utilize thin layers of mesogenic materials, typically less than 10 µm. However, emerging non-display applications will require thicker, i.e., greater than 100 µm, layers of liquid crystals. Although electro-optical performance of relatively thin liquid crystal cells is well-documented, little is known about the properties of thicker liquid crystal layers. In this paper, the electro-optical response of dual-frequency nematic liquid crystals is studied using a broad range (2−200 µm) of the cell thickness. Two regimes of electro-optical switching of dual-frequency nematics are observed and analyzed.